Hanoi - Le village du Kinh-Luoc (tan p) - Auteur inconnu (Wikimedia Commons, 1945)
Notice image issue de Wikimedia Commons pour la dmo du fonds documentaire. Titre: Hanoi - Le village du Kinh-Luoc (tan p). A postcard depicting the tomb of the Nguy?n Dynasty Mandarin (and the Viceroy of Tonkin) Hong Cao Kh?i in the city of Hanoi, in the French protectorate of Tonkin.
Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale